Scientific bases for definingthe coastal zone of Quang Binh, Quang Tri, Thua ThienHue provinces - Nguyen, Hieu (VNU, 2014)
Vietnam has more 3000km of coastline and the features of the coastal zone in various areas (Northeast area, Red River Delta, Central Region and Mekong River Delta) are als o different. Therefore, it is necessary to study specific characteristics of each area and find out the suitable boundaries for the coastal zone. The legal basis related t o Vietnam’s territorial sovereignty on the sea, the t ypical natural resour ces of the Quang Binh - Quang Tri - Thua Thien Hue coastal zone (Quaternary sand terraces, sand dunes, lagoons, sea grass, coral reef…), administrative organization, project ability, the capacity of data inheritance, and the experiences of successful I CZM projects in Vietnam and in the world, all are scientific bases for defining the coastal zone of Quang Binh, Quang Tri, Thua Thien Hue provinces in general and the study area of project KC 09.08/06-10 in particular. The landward portion of the study area includes 206 communes of Quang Binh, Quang Tri, Thua Thien Hue provinces that have their entire or most area l ocated east of the 25m contour line. The seaward boundar y of the pr oject study area is found mainly along the 30m isobath. The boundary i s extended to the 50m isobath (the limit of coral ecosystem distribution) around Con Co Island. The total study area of the project KC 09. 08/06-10 is 9, 837 km sq.